2022
DOI: 10.3991/ijim.v16i22.34151
|View full text |Cite
|
Sign up to set email alerts
|

Using Android-Based E-Module to Improve Students’ Digital Literacy on Chemical Bonding

Abstract: Digital literacy is critical in the current era of digitalization. Therefore, students are required to be digitally literate. This study aims to improve students’ digital literacy using an android-based e-module in chemical bonding. This study used a quasi-experimental method with a pre-experimental design that included a pretest and posttest for one group. For this study, 70 preservice teachers (10 males and 60 females) from the Department of Chemistry Education at a private university in Indonesia were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
2
10
0
2
Order By: Relevance
“…In this study, we found that students' literacy and numeracy in both chemistry and biology can be improved using augmented reality game-based learning (ARGBL). The results of the present study were consistent with prior studies [35] [36] [37]. The use of mobile technology to support literacy programs in education is based on the fact that students need autonomy and flexibility to encourage their self-regulation.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that students' literacy and numeracy in both chemistry and biology can be improved using augmented reality game-based learning (ARGBL). The results of the present study were consistent with prior studies [35] [36] [37]. The use of mobile technology to support literacy programs in education is based on the fact that students need autonomy and flexibility to encourage their self-regulation.…”
Section: Discussionsupporting
confidence: 91%
“…PhenoBL media as a digital module can be used as an alternative to strengthening students' necessary thinking skills [42]. Interactive modules can improve students' essential thinking skills [43] [87]. Critical thinking and student participation in interactive video classes are much higher than in typical lecture groups [44].…”
Section: Introductionmentioning
confidence: 99%
“…Today, significant people in the field of cutting-edge technology are paying attention to the concept of the Metaverse and its potential implications for the academic world (Dewi et al, 2022). Metaverse technology is increasingly used in various virtual contexts, including games, education, and community initiatives (Mistretta, 2022).…”
Section: Metaverse Applications In Education and Learningmentioning
confidence: 99%